Evaluation of Graded Levels of Fermented Plant Protein (Proteger®) on Extrusion Processing and Diet Utilization in Young Cats - Youhan Chen; Charles Gregory Aldrich (Animals)
This study evaluated fermented plant protein (FPP) for extrusion performance and its effects on diet utilization in adult cats. Four diets were formulated: a control with 15% soybean meal (SBM) and three diets replacing soybean meal at 5%, 10%, and 15% with FPP (5FPP, 10FPP, and 15FPP). Diets were extruded using a single-screw extruder, with data and samples collected at 15 min intervals. Twelve cats participated in a 4 × 4 Latin square design, with 9 days of diet adaptation followed by 5 days of total fecal collection for nutrient digestibility and colonic fermentation analysis. Processing effects of FPP inclusion were minimal. The kibble sectional expansion index was lowest for SBM (2.50) and highest for 15FPP (2.82; p < 0.05). Fecal moisture increased (p < 0.05) in cats fed 15FPP. The apparent total tract digestibility of protein was greatest (p < 0.05) in cats fed 15FPP. The fecal ammonia concentrations increased linearly (p < 0.05) with FPP, while total fatty acid concentrations were lower (p < 0.05) in cats fed 10FPP compared to SBM. Cats preferred (p < 0.05) 10FPP over SBM as measured by the intake ratio. The FPP inclusion (up to 15%) did not adversely affect processing, stool quality, or nutrient digestibility. Diets with 5–10% FPP tended to reduce hind-gut fermentation.